Istikhdaam al-Thariqah al-I’tiyaadiyyat fi Ta’lim al-Khath li Thullaab al-Jaami’at استخدام الطريقة الاعتيادية في تعليم الخط لطلاب الجامعة - Multazam; Al Anshory, Abdul Muntaqim; Sahrul Muhamad; Intan Karima (Journal of Calligraphy, 2024)
This study aims to find out the use of learning techniques of I’tiyadiyah method and to find out the effectiveness of the use of learning techniques in I'tiyadiyah method in khat learning in Arabic Education Study Program at Universitas Islam Negeri Maulana Malik Ibrahim Malang Malang. The research method used by researcher is quantitative method, and the approach used is experimental approach which consists of groups namely experimental group and control group. The results of this study are: 1). The application of I'tiyadiyah method learning techniques is as follows: the researcher explained I'tiyadiyah method first, in which the writing method used a dry pen (ordinary pen) and did not use khandam and ink, and the media used millimeter block books. 2). The use of I'tiyadiyah method learning technique is effective in learning khat in PBA Study Program at UIN Maulana Malik Ibrahim Malang. It is known from the results of t-test. It shows that the results of t-count is 12.43 greater than t-table (table significance) which is 5% = 1,980. It indicates that Ha is accepted, or in other words that the use of I'tiyadi Method learning technique is effective in learning khat in Arabic Language Education Study Program at Universitas Islam Negeri Maulana Malik Ibrahim Malang Malang.